Netnography Study: Racism Against TikTok Account @mingokwamkilama16 - Inggi Miya Febty; Zuly Qodir (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
The purpose of this study is to find out what types of racism are experienced by TikTok users who have an account named @mingokwamkilama16. This research is to find out what racist words are expressed by TikTok users. Besides that, it also wants to find out what types of racism are happening. This study uses a descriptive qualitative approach to analyze social media data, namely with NVivo 12Plus to analyze TikTok social media content and data. The data is taken from the TikTok account @mingokwamkilama16, consists of 5 contents, and gets data of 50 discriminatory comments. The results show that the Papuan tribe often experiences acts of racism when using social media, such as creating content on the Tiktok application, and creating an @mingokwamkilama16 account, which is often discriminated against by other Tiktok users. Of the three indicators studied, the most dominant is discrimination on race, which reaches 70% of the data. This shows that racial discrimination is prevalent, this attitude can make account users feel hurt, and many are physically disturbed. Papuan people are also part of Indonesia, but Indonesian people are also racist toward them. There are still many Tiktok users who lack education about Indonesian races.